The Correlation Between the Arm Muscle Strength to Passing Skill in Handball Games - Firdaus Hendry Prabowo Yudho; Muhammad Alvin Nur El Hakim; Dhika Bayu Mahardhika; Rahmat Iqbal; Setio Nugroho; Akhmad Dimyati (Universitas Suryakancana, 2021)
This research aims to find out the relationship of arm muscle strength to passing skills in handball games in members of SME (Student Activity Unit) Suryakancana Cianjur University. The method used in this study used quantitative methods of this type of method with a sample number of 30 people. Data collection uses a push pull dynamometer to then perform data normality tests, data correlation tests, and simple linear regression tests. The results of the study on the data normality test obtained significant values of variableS X, 390 and variable Y of ,257 both values showed that the value exceeded a significant level of >0.05 then the data was normal distribution. Based on the results of the correlation test there is a significance value of 0.09 indicating that the data has a relationship. The results of a simple linear regression test obtained an r-square value of 0.323 that there was an influence on the relationship of arm muscle strength to the passing ability in handball games by 0.323%.Key words: Arm strength, Passing ability, Handball, Sports Skill, Motor ability